2020
DOI: 10.12688/wellcomeopenres.15681.1
|View full text |Cite
|
Sign up to set email alerts
|

ACORN (A Clinically-Oriented Antimicrobial Resistance Surveillance Network): a pilot protocol for case based antimicrobial resistance surveillance

Abstract: Background: Antimicrobial resistance (AMR) / drug resistant infections (DRIs) are a major global health priority. Surveillance data is critical to inform infection treatment guidelines, monitor trends, and to assess interventions. However, most existing AMR / DRI surveillance systems are passive and pathogen-based with many potential biases. Addition of clinical and patient outcome data would provide considerable added value to pathogen-based surveillance. Methods: The aim of the ACORN project is to develop an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Wellcome is currently backing the ACORN project—organised by Oxford University in the UK and Mahidol University in Thailand—to establish an active surveillance network for AMR across low and middle income countries 9. The idea is to collect data in a way that better integrates clinical information about each patient’s health condition with the microbiology laboratory results.…”
Section: Resource Gonementioning
confidence: 99%
“…Wellcome is currently backing the ACORN project—organised by Oxford University in the UK and Mahidol University in Thailand—to establish an active surveillance network for AMR across low and middle income countries 9. The idea is to collect data in a way that better integrates clinical information about each patient’s health condition with the microbiology laboratory results.…”
Section: Resource Gonementioning
confidence: 99%
“…In this study, the 21 EIS that identified a specific country of implementation, were mostly located in HICs (n=17), with a smaller number implemented in LMICs (n=4). Additionally, two of the six EIS which included a range of countries were found to involve predominantly LMICs (such as Southeast Asian countries), 43 44 demonstrating a slight overall increase in the presence of EIS in LMICs over the past 5 years since a previous review in 2017 17 of a similar scope. The growing number of EIS being deployed in LMICs in recent years may be due to the heightened awareness at national and global levels about AMR, increased access to digital health technologies in LMICs, availability of international funding initiatives for implementing EIS as components of AMR surveillance or increased demand for AMR data in recent years.…”
Section: Discussionmentioning
confidence: 85%
“… 16 By improving the standardised reporting of routine microbiological and clinical surveillance data and ensuring open access to underlying data sources, these inherent challenges to antibiogram and WISCA methodology (and their subsequent clinical and policy-guiding utility) could be substantially improved. 48 …”
Section: Discussionmentioning
confidence: 99%